HUBUNGAN TINGKAT PEMAHAMAN DAN KEPATUHAN IBU HAMIL TENTANG PENTINGNYA PEMERIKSAAN ANC DENGAN MENERAPKAN PROTOKOL KESEHATAN COVID 19 DI WILAYAH KERJA PUSKESMAS RUMBIA KECAMATAN RUMBIA - Jumrana Jumrana; Kasmawati Kasmawati (Jurnal Rumpun Ilmu Kesehatan, 2022)
Until now, knowledge about COVID-19 infection in relation to pregnancy and the fetus is still limited and there have been no recommendations issued by WHO specifically for the treatment of pregnant women with Covid 19. Objective: Relationship between the level of understanding and compliance of pregnant women regarding the importance of ANC examinations with Implementing the Covid-19 Health Protocol in the Rumbia Pueskesmas Work Area, Rumbia District, Jeneponto Regency. The type of research used is a cross sectional study. The sample was 39 pregnant women who visited ANC in the working area of ​​the Rumbia Health Center, Rumbia District, Jeneponto Regency. The results of the research show that there is a relationship between pregnant women's compliance regarding the importance of ANC examinations and implementing the Covid-19 health protocol in the Rumbia Pueskesmas work area, Rumbia District, Jeneponto Regency with a p value = 0.000 < α 0.05, there is a relationship between the level of understanding of pregnant women about the importance of ANC examinations. by implementing the Covid-19 health protocol in the Rumbia Pueskesmas work area, Rumbia District, Jeneponto Regency with a p value = 0.000 < α 0.05. Conclusion: there is a relationship between the compliance of pregnant women and the level of understanding of pregnant women about the importance of ANC examinations by implementing the Covid-19 health protocol in the work area of ​​the Rumbia Pueskesmas, Rumbia District, Jeneponto Regency. Suggestions: For mothers who will visit the Rumbia Community Health Center, Rumbia District for pregnancy checks, they are expected to always wear a mask, in this case knowing the importance of the Covid-19 health protocol.